Instructional Guidelines for Promoting Geo-literacy of Upper Secondary School Students - Singsatorn, Natchayakorn; Sawekngam, Wichai (An Online Journal of Education, 2024)
The purposes of this descriptive research were: 1) to study the existing conditions and problems, and 2) to propose instructional guidelines for promoting geo-literacy among upper secondary school students. Data were collected by using surveys and qualitative interviews with a sample group, consisting of 312 high school social studies teachers. From this group, there were 10 teachers who specialized in teaching geography. The research tools included a questionnaire and interview form, and data were analyzed using descriptive statistics percentages, arithmetic average standard deviation and content analysis. This study found that, in terms of teacher preparation, teachers lack up-to-date knowledge and skills in teaching geography and lack continuous support for knowledge and skill development. In terms of learning objectives, teachers lack an understanding of the components of geo-literacy, resulting in a failure to link learning objectives with geo-literacy components. In terms of teaching activities, Teaching lacks variety and interest, and there is a lack of technology use in teaching activities. In terms of media and learning resources, Teachers still lack modern media and learning resources. There is also inconvenience in using media and a lack of facilities that support the use of geographical media and learning resources. In terms of assessment and evaluation, there is a lack of effective assessment methods and tools. The proposed instructional guidelines for promoting geo-literacy are: Teachers should develop their knowledge and skills in teaching geography through workshops and continuous learning. Teachers must clearly define learning objectives that cover the components of geo-literacy. They should organize teaching activities using geospatial technology and hands-on practice, employ the geo-inquiry process and fieldwork. Teachers should use media and learning resources that utilize geospatial technology. They should design assessments that link with the components of geo-literacy and use authentic assessment methods with scoring rubrics.